INLAND PORTS AND LINK TO ECONOMIC DEVELOPMENT IN GHANA: A LITERATURE REVIEW - DENIS ATEHNJIA; WISDOM NKONU; COSMOS KOUFIE (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents a literature review highlighting the factors that influence the development of an inland port and its economic benefitsto small communities in Ghana. A criticalreview reveals great research has been carried outto encourage planners and investors interested in understanding the various elements that are particular to a developing nation in the construction of an inland port. Further analysis reveals that several aspects of dependence on transit neighbors are also essential in highlighting the need for inland port classification